Longitudinal trajectories of diet quality and subsequent mortality among Chinese adults: results from the China health and nutrition survey 1997-2015 - Ming-wei Liu; Sarah A. McNaughton; Qi-qiang He; Rebecca Leech (BMC, 2021)
Abstract Background China has witnessed a significant nutritional transition. However, there is a gap in the literature investigating the association between change of diet and mortality among Chinese. Thus, we aimed to explore the longitudinal trajectories of diet quality over 10 years (from 1997 to 2006) and the subsequent risk of death till 2015 among Chinese adults. Methods Data from the China Health and Nutrition Survey were analyzed in 6398 adults. Dietary intake was assessed using three consecutive 24-h recalls. Diet quality was assessed by the Chinese Healthy Eating Index (CHEI), which includes 17 components and is based on the Dietary Guidelines for Chinese. Latent Class Growth Analysis was conducted to derive trajectories of diet quality over 10 years. Cox proportional hazard regression was used to calculate hazard ratios for total mortality. Results Four distinct CHEI trajectories were identified: 1) worsening; 2) low-moderate-low; 3) improving; 4) high-moderate-high. Group 3 had the lowest mortality rate (5.6%) in the subsequent 9 years, while the groups with worsening or low diet quality had a higher mortality rate (Group 1: 7.5%; Group 2: 10.8%). In the fully adjusted model, compared to group 2, mortality rates were lower for group 3 (RR = 0.73; 95% CI: 0.55, 0.97) and group 4 (RR = 0.76; 95% CI: 0.59, 0.98). No associations with mortality were found for the group 1, when compared to group 2. Conclusions Long-term improved diet quality and adherence to the Dietary Guidelines for Chinese may decrease the risk of death in Chinese adults.